How to Determine the Customer Purchase Decision at Kopi Tikum Shop, South Jakarta - Ikramina Larasati Hazrati Havidz; Dika Ajy Nugraha; M. Havidz Aima; Hernawati. W. Retno Wiratih (Dinasti Publisher, 2023)
Business development in the digitalization era has an impact on in the business sector. At present time, business sector perceived the impact of intense competition. This competition requires entrepreneurs to act quickly and precisely at present dynamic business competition. Current study aims to determine the effect of product quality (ProQu), Price Suitability (PriSu) and Service quality (ServiQu) on purchasing decisions (PurchDe) at Kopi Tikum, South Jakarta. SEM is the method used to test the hypotheses proposed in the study. The results of this study indicates that ProQu, PriSu, and ServiQu have a positive and significant effect on purchasing decisions. Meanwhile, ProQu, PriSu, and ServiQu simultaneously have effect on PurchDe. Therefore, it is found that the purchase decision of the Kopi Tikum customer occur as the effect given by ProQu, PriSu, and ServiQu. In order to keep the business run, Kopi Tikum is recommended to leverage the product quality. The study may also provide new insight to the practical managerial that runs their business in the field of coffee shop.